Analisis Disiplin Belajar pada Peserta Didik Kelas V SD Negeri Sekip II Surakarta Tahun Pelajaran 2019/2020 - Aglen Femmy Titirloloby; Sri Handayani; Anggit Grahito Wicaksono (Departement of Mathematics Education, 2023)
The purposes of this study are: 1) to analyze learning discipline in participating in timely online learning for fifth-grade students at SDN Sekip II Surakarta. 2) To analyze the discipline of learning in submitting assignments on time at SDN Sekip II Surakarta. The type of research used is descriptive qualitative. The subjects used in this study were students in class V of Sekip II State Elementary School Surakarta for the 2019/2020 academic year. Data collection methods are observation, structured interviews, and documentation. Observations were used to obtain initial data obtained from class teachers regarding the learning discipline of fifth-grade students at SDN Sekip Surakarta. Structured interviews were used to obtain the required information. Documentation in the form of student name data, photos of research activities, and school profiles. The validity of the data uses source triangulation and technical triangulation. Data analysis in this study includes data reduction. Presentation of data, and verification. Based on the data analysis that has been carried out, the following results are obtained: 1) the learning discipline of students in participating in online learning in class V SD Negeri Sekip II Surakarta is said to be good. Some students are disciplined in participating in online learning and some students are not yet disciplined in participating in online learning. Students who are already disciplined in taking part in online learning, that is, always take part in learning on time and take part in learning in an orderly manner. Meanwhile, students who are not disciplined in participating in online learning are not punctual in participating in learning and are not orderly when participating in learning. 2) the learning discipline of students in submitting assignments on time in class V SD Negeri Sekip II Surakarta is said to be good.